Mathematical E-Modules in the Digital Era: A Bibliometric Analysis of Trends, Gaps, and Opportunities (2015–2025) - Jajang Rahmatudin; Yaya S. Kusumah; Bambang Avip; Rasilah Rasilah (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
The integration of digital technology into school learning processes has become a significant trend, with e-modules emerging as an essential form of digital learning resources. This study aims to identify research trends related to the use of e-modules in mathematics education at schools. A bibliometric analysis was employed, involving the mapping of research trends through metadata analysis. This study applied a systematic quantitative method, with metadata retrieved from Scopus and Google Scholar databases using the Publish or Perish software, and further analyzed using VOSviewer. The findings, based on Scopus and Google Scholar data, reveal that research on e-modules in mathematics learning is largely dominated by the ADDIE model, with most applications occurring at the secondary school level. However, relatively few studies have focused on 21st-century skills. The most recent research topics on e-modules in mathematics education, as reflected in keyword trends, include interactive e-modules, realistic mathematics education, ethnomathematics, and mathematical literacy. In contrast, areas such as computational thinking, mathematical reasoning, mathematical literacy, augmented reality (AR), artificial intelligence (AI), game-based learning, and higher-order thinking skills (HOTS) remain underexplored. These gaps indicate broad opportunities for future research on the use of e-modules in mathematics learning